Candida in oral lichen planus - Santosh Gowdru Shivanandappa; I M Ali; C Sabarigirinathan; Lata S Mushannavar (Wolters Kluwer Medknow Publications, 2012)
Introduction: Lichen planus is a human exclusive, chronic inflammatory disease affecting skin and mucosa, particularly oral mucosa affecting the stratified squamous epithelia. Epithelial alterations in oral lichen planus (OLP) may lead to superimposed Candida infection, especially the normal flora Candida albicans. Therefore, this study was designed to assess the prevalence of Candida infection in OLP lesions. Materials and methods: Thirty-four OLP patients were subjected to clinical, mycological and histopathological investigations for the presence of candidal organisms. The data obtained was analyzed statistically using Chi-square test and Student's t-test. Results: Among the 34 patients in the study group 15 (44.11%) showed positive candidal culture on Sabouraud's dextrose agar medium and none of the 34 histological sections of OLP showed candidal hyphae on Periodic acid-Schiff staining. No significant association of positive candidal culture with respect to symptoms and patterns of lichen planus were found. Conclusion: Candidal infection in OLP is insignificant.